Tinjauan Yuridis Pemungutan Pajak Terhadap Online Shop - Wahyuni Safitri; Faradina Alya Safira (Yuriska: Jurnal Ilmiah Hukum, 2021)
This study aims to determine the arrangement of tax collection againstOnline Shop what researchers did in Samarinda City. This research is a Normative Law research that originates from primary and secondary legal materials. The results of this study indicate that the arrangement of tax collection ononline shop as Taxpayers are Law Number 36 of 2008 concerning Income Tax, Government Regulation Number 23 of 2018 concerning Income Tax on Income from Business Received or Earned by Taxpayers with Certain Gross Turnover and tax provisions related toecommerce has been confirmed in the Circular Letter of the Director General of Taxes Number SE-62/PJ/2013 Concerning the Affirmation of Tax Provisions on TransactionsEcommerce,in its implementation there is no specific data collection ononline shop as a Taxpayer. So it is suggested that the government can issue laws and regulations that can cover all forms of e-commerce in order to create a good tax payment mechanism.